1993
DOI: 10.1042/bj2910257
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the glucose transporter GLUT4 in the muscular dystrophic mdx mouse

Abstract: Glucose transporter protein levels have been investigated in mdx and control (C57Bl/1O) mice. Crude membrane fractions (microsomes plus plasma membranes) were prepared from skeletal muscle, heart, diaphragm and brain of 5-6-week-old and 6-7-month-old control and mdx mice. Using Western blot analysis with C-terminal-specific anti-peptide antibodies, we investigated the glucose transporters GLUT4 in the different muscle tissues and GLUTI in brain. In skeletal tissue from the hindlegs, GLUT4 was increased by -55 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
1
7
1
Order By: Relevance
“…Total RNA and protein concentrations in the two groups were not different. This is not the first study to show discordance with respect to GLUT4 mRNA and protein concentrations2, 5, 17; however, we show that there is an inverse relationship between the two variables in patients with MD. Several studies have demonstrated that the relationship between GLUT4 transcription and translation is not always tightly coupled under conditions of metabolic stress.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Total RNA and protein concentrations in the two groups were not different. This is not the first study to show discordance with respect to GLUT4 mRNA and protein concentrations2, 5, 17; however, we show that there is an inverse relationship between the two variables in patients with MD. Several studies have demonstrated that the relationship between GLUT4 transcription and translation is not always tightly coupled under conditions of metabolic stress.…”
Section: Discussioncontrasting
confidence: 60%
“…Two studies involving altered physiological states and GLUT4 expression in rats have shown no correlation between muscle GLUT4 mRNA and protein concentration 2, 5. Using the mdx murine model of Duchenne muscular dystrophy, investigators have reported discordant results with higher GLUT4 protein and lower GLUT4 mRNA levels when normalized to total RNA 17. The incongruence between the GLUT4 mRNA and protein results in the current study sends an important cautionary message to researchers in the area of physiology and medicine where there is a tendency to imply that changes in mRNA abundance lead to directionally similar changes in protein content, especially in gene array studies 22, 25…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being the voltage sensor for excitation-contraction coupling, the skeletal muscle Ca 2ϩ channel has a privileged connection to regulation of gene expression that bypasses the Ca 2ϩ signal generated by the sarcoplasmic reticulum and ryanodine-sensitive Ca 2ϩ release channels (5). Reduction in this Ca 2ϩ current may be partially responsible for the disruptions in gene expression observed in the mdx mouse and in individuals with Duchenne and Becker muscular dystrophies (52)(53)(54)(55)(56). Because trophic effects on gene expression are important in maintenance of muscle fiber function and structural integrity, alteration in the regulation of gene expression by voltage-gated L-type Ca 2ϩ currents may contribute significantly to the progressive muscle dysfunction and cell death associated with these diseases.…”
Section: Effects Of Pka On Voltage Dependence Of Ca 2؉ Channel Activimentioning
confidence: 99%
“…Genotype/phenotype Mean weight, g Percentage of large animals mals of parental strain (C57Bl/10Sn), which was previously demonstrated for 6-7-month-old mutant and normal black females [10].…”
Section: Resultsmentioning
confidence: 95%